Social Action Of MLBB Gaming Community On Trash Talking Culture Among Youth OF Denpasar City - Antara, I Gede Agus Wisnu; Punia, I Nengah; Aditya, I Gusti Ngurah Agung Krisna (JURNAL ILMIAH SOSIOLOGI: SOROT, 2025)
Mobile legend is an online games widely played by gamers in Indonesia. It is become one of the most downloaded online games on smartphone. As the game continues to grow, the behavior of trash talking has also become increasingly prevalent within the game. This research uses a qualitative approach with a descriptive-explanative research type. The theory used in this study is Talcott Parsons theory of social action. This study examines the social action of the mlbb gaming community related to the culture of trash talking among youth in Denpasar City. Based on the findings, appopriate action are needed from the mlbb gaming community to address the growing culture of trash talking. Action that the community can take to reduce trash talking include not overly normalizing such behavior towards other, and maintaining respectful and non-aggresive interaction with fellow players. This study also highlights several factors that encourage players to engage in trash talking, such as provocating during game play and frustation with underperfomming teammates . Keywords: MLBB Community, Trash Talking, Youth, Social Action